WOMEN, GENDER, AND ISLAM IN AFRICA AND BEYOND - Eltantawi, Sarah (Journal of law and religion, 2014)
Scholars of Islamic law, gender, and Africa will be pleased with the arrival of two important new volumes that are bold in their bringing together of ethnographic data with legal history and analysis. Margot Badran's Gender and Islam in Africa: Rights, Sexuality, and Law, and Christina Jones-Pauly and Abir Dajanfi Tuqan's Women under Islam: Gender Justice and the Politics of Islamic Law collectively advance a movement in Islamic legal studies that focuses on interdisciplinary explorations into the ways particular constructions of Islamic law are foregrounded and reified in accordance with the existential impulses and demands of a particular society at a particular time, what we might call the "hermeneutic of experience." I would argue that gender functions as the category that most regularly exposes the limitations of various historically situated concepts of orthodoxy, and these books bear out this claim.